Factors Challenging the Spiritual Rehabilitation of Iranian Men Affected by Natural Disasters: A Qualitative Study - Nejati-Zarnaqi, Bayram (Journal of religion and health, 2022)
Spiritual health is one important dimension of human health. Natural disasters, however, can adversely affect human spiritual health. One of the undeniable requirements of disaster management is the spiritual rehabilitation of victims to help them recover to their pre-disaster health conditions. This study aimed to explore the factors challenging the spiritual rehabilitation of Iranian men suffering from natural disasters based on the experiences of key informants. The participants were 19 spiritual health experts in post-disaster spiritual rehabilitation. Participants were selected using a purposive sampling method until data saturation was reached. The data were collected through semi-structured interviews and analyzed using Granheim and Lundman (2004) content analysis method. The factors challenging men’s spiritual rehabilitation were classified into 6 main categories and 16 subcategories. The extracted categories included (i) correcting victims’ perspectives, (ii) describing God’s characteristics, (iii) seeking help from God, (iv) strengthening spiritual beliefs, (v) psychological factors, and (vi) tranquility factors. Our findings identified the important factors challenging the spiritual rehabilitation of the men victimized by natural disasters, which needed to be considered by responsible organizations and health sectors. Particularly, the organizations in charge of disaster management should take necessary measures and plans during the post-disaster phase to restore people’s spiritual health. Spiritual health, currently a neglected dimension of health, should be considered people’s in parallel with physical, psychological, and social health dimensions. Our results can be helpful in developing action plans for delivering a comprehensive spiritual rehabilitation service, which would help to lead to the full rehabilitation of victims after natural disasters.